The impact of point-of-care transthoracic echocardiography on management of patients presenting for emergency surgery in a resource-limited setting - Munsie, Robert David (Department of Anaesthesia and Perioperative Medicine, 2023)
Objective: In this study of patients presenting for non-cardiac, emergency surgery in a resource limited setting, we aimed to evaluate the impact of routine preoperative transthoracic echocardiography on perioperative management. Design: A prospective before- and after-study of adult patients presenting for emergency, non-cardiac, non-obstetric surgery. Setting: The study was performed at an academic hospital in Cape Town, South Africa. Participants: Consenting patients over 18 years of age presenting for emergency surgery enrolled via convenience sampling during working hours over a 10 day period. Interventions: Basic and advanced Focused Assessment Transthoracic Echocardiography (FATE) was performed to evaluate ventricular function, valvular pathology and fluid status. After completing an assessment and treatment plan, the FATE findings were disclosed to the treating anesthetist. A post FATE plan was subsequently completed. Measurements and Main Results: A total of 67 patients were scanned with a change in management detected in 55% of cases. Thirty-nine percent of these alterations were in response to fluid management strategies with 31% of patients scanned being assessed as hypovolemic. There was a statistically significant link between patient volume status and change in perioperative management (p=0.0003). The presence or absence of valvular pathology also led to a significant association with change in management (p=0.020), most commonly in relation to the decision to proceed with surgery or the use of additional monitoring. Conclusion: This observational study of adult patients presenting for emergency surgery in an upper middle-income country demonstrates that routine preoperative transthoracic echocardiography has an impact on perioperative anesthetic management.